Dampak Daya Saing dan Strategi Pemasaran terhadap Kinerja Perusahaan pada PT. KSE - Ahmad, Syaiful; Nugraha, Krisma Eka Wahyu; Arrozaq, Muhammad Ilham Fatah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
The phenomenon that occurs in the company's performance where the performance targets set by the company have not been achieved and the HR performance at PT KSE has not been optimal. This study aims to determine and analyze the influence of competitiveness and marketing strategy on company performance at PT. Energy Source Works. This research design uses a cross-sectional design. Cross-sectional is the study of independent and dependent variables measured simultaneously. The sample of this study was 90 PT KSE service users from 18 service user companies taking as many as 5 people per company with a total of 90 people. The analysis tool used is SmartPLS Software. The results showed that there was a positive and significant influence of competitiveness on the company's performance at PT. Karya Sumber Energy, with a coefficient value of X1 of 0.200 with T calculated > T table, Has a positive and significant influence of marketing strategy on company performance at PT. Karya Sumber Energy, with a coefficient value of X2 0.702 with T calculated > T table and There is a positive and significant influence of competitiveness and marketing strategy together on company performance at PT. Energy Source Work, with a coefficient of determination value of 0.735 or 73.5% with F calculated > F table